Delimitar y gobernar las aguas de Lima: relaciones urbano-rurales y rivalidades administrativas en Lima colonial - Bell, Martha (2016)
Lima’s city wall was completed in 1687, creating a physical boundary between the urban space and its rural surroundings. Yet well before this date, the division between city and countryside had been established. Water governance wasone arena in which this can be observed. Officially, all water in Lima and its rural surroundings fell under the jurisdiction of Lima’s cabildo. However, the viceroy and Real Audiencia were also frequently involved in water governance, sometimes in direct conflict with the cabildo. This article analyzes the debate over the roles of these branches of government during the entire colonial period.